تحقيق المناط وأثره في توجيه فتاوى المعاملات المالية الصادرة عن مجلس العلماء الإندونيسي : دراسة تحليلية - مبارك، نور ألفين (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This research is an objective study on Tahqiq al Manat, its salient features and limitations. This research studies the importance of Tahqiq al Manat towards the issuance of fatwa (Islamic edict). By definition, Tahqiq al Manat is about establishing a link between (or connecting) revelation to reality, as the relevation descends gradually according to circumstances and general concerns, the function of Tahqiq al Manat is manifested in implementing laws and acting as the law giver explanation towards every occurrence. There have been conflicts and disagreements between fatwas on some new issues. These major differences have posed a danger as it threatens the unity of ummah and the harmony among them. In contemporary times, a mufty who issues fatwas is obligated to master Tahqiq al Manat. Without it, fatwas become contentious among scholars as well as the public. This research aims at studying the important role played by Tahqiq al Manat in directing and guiding fatwa in a way that is in line with the Law giver intention. Pursuant to the nature of the topic, the research employs in-depth investigation (al istiqraiy) and analytic methodology in dealing with Tahqiq al Manat and its role in guiding fatwas. The research area is limited to the fatwas of the National Advisory Board of Indonesian U'lama‛ Council (DSN-MUI) on the field of financial transtractions because of the obscurity as well as the importance of them. This research shows the important role played by Tahqiq al Manat in issuance of fatwas since the root of discrepancies and differences in laws is the difference in terms of the Tahqiq al Manat applied to the problems. In addition, this study also shows clear distinction between the deliberate, hardworking mufty and the hasty, negligent one. The main recommendation of this study is for Uṣul al Fiqh teaching to give more attention and deliberation on the Tahqiq al Manat by the way of extra polating applications.